Urea to albumin ratio is a predictor of mortality in patients with septic shock - Pereira, Amanda Gomes [UNESP]; Costa, Nara Aline; Gut, Ana Lúcia [UNESP]; Azevedo, Paula Schmidt [UNESP]; Tanni, Suzana Erico [UNESP]; Mamede Zornoff, Leonardo Antonio [UNESP]; Rupp de Paiva, Sergio Alberto [UNESP]; Polegato, Bertha Furlan [UNESP]; Minicucci, Marcos Ferreira [UNESP] (Elsevier, 2021)
Background: The purpose of this study was to evaluate urea to albumin ratio (UAR) as predictor of mortality in patients with septic shock. Methods: We included all individuals aged ≥ 18 years, with the diagnosis of septic shock at Intensive Care Unit (ICU) admission. Laboratorial and clinical data was recorded within the first 24 h of the patient's admission. Serum urea and albumin concentration were used for UAR calculation. All patients were followed during their ICU stay and the mortality rate was recorded. Results: 222 patients were included in the analysis; the mean age was 62.3 ± 15.1 years and 66% were male. Mortality rate during the ICU stay was 59.9% and the median UAR was 40.7 (24.5–66.1). The UAR was also higher in patients who died in the ICU and was positively correlated with APACHE II, SOFA score and CRP. The ROC ICU mortality development (AUC: 0.617; CI 95%: 0.541–0.693; p: 0.003) at the cutoff of ≥47.25. Furthermore, UAR values were associated with ICU mortality when adjusted by age, sex and APACHE II (OR: 1.011; CI95%:1.000–1.022; p = 0.043) and when adjusted by lactate (OR: 1.014; CI95%:1.003–1.024; p = 0.009). Conclusions: Our data suggest that UAR could play a role as predictor of ICU mortality in patients with septic shock.
Keywords: Mortality; Septic shock; Ureia/albumin ratio